The progress and prospects of targeting the adenosine pathway in cancer immunotherapy - Yuying Yang; Lin Zhu; Yantao Xu; Long Liang; Li Liu; Xiang Chen; Hui Li; Hong Liu (Biomarker Research)
Abstract Despite the notable success of cancer immunotherapy, its effectiveness is often limited in a significant proportion of patients, highlighting the need to explore alternative tumor immune evasion mechanisms. Adenosine, a key metabolite accumulating in hypoxic tumor regions, has emerged as a promising target in oncology. Inhibiting the adenosinergic pathway not only inhibits tumor progression but also holds potential to enhance immunotherapy outcomes. Multiple therapeutic strategies targeting this pathway are being explored, ranging from preclinical studies to clinical trials. This review examines the complex interactions between adenosine, its receptors, and the tumor microenvironment, proposing strategies to target the adenosinergic axis to boost anti-tumor immunity. It also evaluates early clinical data on pharmacological inhibitors of the adenosinergic pathway and discusses future directions for improving clinical responses.